A Comparison of Frequency-Dependent Soil Models: Electromagnetic Transient Analysis of Overhead Transmission Lines Using Modal Decomposition - Garbelim Pascoalato, Tainá Fernanda [UNESP]; Justo de Araújo, Anderson Ricardo; Leon Colqui, Jaimis Sajid; Kurokawa, Sérgio [UNESP]; Pissolato Filho, José (MDPI, 2022)
This article investigates the influence of four causal frequency-dependent (FD) soil models and their impact on the responses of a multiphase overhead transmission line (OHTL) with ground wires, generated by a lightning strike. The FD models proposed by Longmire-Smith (LS), Messier (M), Portela (P) and Alípio-Visacro (AV) are considered. The ground-return impedance and admittance matrices are computed with the Nagakawa approach for both frequency-constant and FD soil models. The frequency-domain modal voltages and time-domain transient voltages are assessed in this work. Modal decomposition technique is used to study the attenuation constant, propagation velocity and voltages for each propagation mode. Simulations are carried out in a frequency range of 100 Hz to 10 MHz, for OHTLs with lengths of 1 and 10 km, on soils of 700 and 4000 Ω·m. Simulation results demonstrated that the Portela (P) model has resulted in more significant variation in the ground-return impedance and admittance, constant attenuation and propagation velocity in which a pronounced variation, especially at the high frequencies, is seen. On the other hand, Longmire-Smith (LS) and Messier (M) have produced similar results in both frequency and time domains. Additionally, the Alípio-Visacro (AV) model has produced intermediate responses, being the model recommended by CIGRÈ WG C4.33. Time-domain induced voltage waveforms obtained with the Portela (P) model has shown pronounced differences, especially at the peak values, for the high-resistive soil. This study demonstrates the importance of considering the FD soil models to assess the transient responses adequately, especially when OHTLs are on high-resistive soils.
Keywords: Electromagnetic analysis; Frequency-dependent soil models; Lightning; Modal decomposition; Multiphase overhead lines